Recruitment of Reverse Transcriptase-Cas1 Fusion Proteins by Type VI-A CRISPR-Cas Systems - Toro, Nicolás; Mestre, Mario Rodríguez; Martínez-Abarca, Francisco; González-Delgado, Alejandro (Frontiers in Microbiology, 2019)
Type VI CRISPR–Cas systems contain a single effector nuclease (Cas13) that exclusively targets single-stranded RNA. It remains unknown how these systems acquire spacers. It has been suggested that type VI systems with adaptation modules can acquire spacers from RNA bacteriophages, but sequence similarities suggest that spacers may provide immunity to DNA phages. We searched databases for Cas13 proteins with linked RTs. We identified two different type VI-A systems with adaptation modules including an RT-Cas1 fusion and Cas2 proteins. Phylogenetic reconstruction analyses revealed that these adaptation modules were recruited by different effector Cas13a proteins, possibly from RT-associated type III-D systems within the bacterial classes Alphaproteobacteria and Clostridia. These type VI-A systems are predicted to acquire spacers from RNA molecules, paving the way for future studies investigating their role in bacterial adaptive immunity and biotechnological applications.